(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the current status of operations of cosmetic spa facilities not licensed by the health sector in Ho Chi Minh City in 2023 and research some affecting factors. Materials and Methods: A Cross-sectional descriptive study with a control group on 20 cosmetic spa facilities with 102 employees who was not licensed by the health sector but have business registration according to the provisions of law in Ho Chi Minh City on the current status of operations in 2023 and randomly divided into two groups. Results: The average number of employees per spa facility is 5.5 ± 1.53. The majority of employees are between the ages of 20 and 40, accounting for 78.4%. Females account for more than males. 44.1% of employees had college or secondary education. The rate of employees who fully know and practice the routine hand washing process in Group I is lower than in Group II, group I is 11.8% and group II is 27.5%. The rate of employees who fully know about skin anatomy, skin care procedures and practices in Group II is higher than Group I. Group I has 7 (13.7%) employees who know about skin care procedures, 6 (11.7%) employees who practice good skin care. Group II has 23 (45.1%) employees who fully know about professional skin care procedures and 21 (41.2%) employees who practice good skin care (p < 0.05). There is a relationship between age group, education level and level of skin care knowledge. Conclusion: Most cosmetic spa facilities are on a small scale. The rate of knowledge, professional practice, degrees, and qualifications of employees at cosmetic spa facilities is low.